تأثير البلازما الغنية بالصفيحات على تسريع الحركة السنية التقويمية لدى الذكور البالغين - حسن حازم; احمد سليمان (Latakia University Journal -Medical Sciences Series, 2019)
Objective: The aim of this study was to evaluate the effect of Platelet Rich Plasma (PRP) in accelerating tooth movement in adult male subjects. Materials and methods: The sample in this clinical trial study consisted of 18 adult male patients with therapeutic need for extraction of maxillary first premolars and maximum canine retraction. By use of split mouth design on maxilla, after 2months of premolars extraction, the injection of prp was performed randomly on one side of maxilla, and no action was applied on the other side Results: Analysis of the rate of canine retraction between the prp application and control sides shows significant differences during the first and second months. Conclusion: The results of this study showed that PRP technique accelerate the rate of orthodontic tooth movement. الهدف: هدف هذه الدراسة تقييم فعالية البلازما الغنية بالصفيحات على تسريع الحركة السنية التقويمية لدى عينة من الذكور البالغين. المواد والطرق: تتألف عينة البحث لهذه الدراسة السريرية من 18 مريض من الذكور البالغين ممن هم بحاجة لعلاج تقويمي مع استطباب قلع الضواحك الاولى وارجاع الانياب العلوية سيتم تقسيم الفك العلوي لنصفين وبالتالي لمجموعتي دراسة,حيث سيتم بعد القلع بشهرين تطبيق البلازما مكان القلع بأحد الجهتين, في حين ستعامل الجهة المقابلة كجهة شاهدة. النتائج: أظهرت نتائج هذه الدراسة وجود فروق جوهرية في متوسط ارجاع الناب العلوي بين الجهتين المدروسة والشاهدة خلال الشهر الاول والثاني. الاستنتاجات: البلازما الغنية بالصفيحات سرعت الحركة السنية التقويمية.